Real-time pH and temperature monitoring in solid-state fermentation reveals culture physiology and optimizes enzyme harvesting for tailored applications - Md Fauzul Kabir; Afranul Qader Ovi; Lu-Kwang Ju (Microbial Cell Factories)
Abstract Enzyme production is crucial for biorefinery applications and the valorization of agricultural residues. However, real-time monitoring of pH and temperature in enzyme-producing solid-state fermentation (SSF) is generally regarded as challenging due to the system’s complexity, with previous studies relying primarily on sacrificial sampling for pH measurements. This study integrates real-time monitoring of pH and temperature with systematic nutrient medium optimization to enhance the SSF enzyme production of α-galactosidase, invertase, pectinase, xylanase, and cellulase by Aspergillus niger NRRL 322 using soybean hulls as the sole carbon source. By capturing dynamic shifts in pH and temperature throughout fermentation, this approach provided important insights into cell growth dynamics, metabolic transitions, and their direct correlations with enzyme production profiles. Comparative analysis of different nutrient media, including nitrogen sources, macronutrient concentrations, and medium strengths, revealed that nitrogen supplementation and balanced macronutrient levels are critical for maximizing enzyme yields. Notably, pH fluctuations were strongly linked to enzyme activity trends, with pectinase and xylanase exhibiting distinct declines after reaching peak levels. The ability to monitor pH and temperature in real time enabled precise optimization of harvest timing for specific enzyme compositions tailored to different industrial applications. These findings establish real-time pH and temperature tracking as a valuable tool for improving SSF process control, paving the way for more efficient and economically viable enzyme production in sustainable biorefineries.